Construction and Interpretation of Prediction Model of Teicoplanin Trough Concentration via Machine Learning - Ma, Pan; Liu, Ruixiang; Gu, Wenrui; Dai, Qing; Gan, Yu; Cen, Jing; Shang, Shenglan; Liu, Fang; Chen, Yongchuan (Frontiers in Medicine, 2022)
Objectives: To establish an optimal model to predict the teicoplanin trough concentrations by machine learning, and explain the feature importance in the prediction model using the SHapley Additive exPlanation (SHAP) method. Methods: A retrospective study was performed on 279 TDM measurements obtained from 192 patients who were treated with teicoplanin intravenously at the First Affiliated Hospital of Army Medical University from November 2017 to July 2021. This study included 27 variables, and the teicoplanin trough concentrations were considered as the target variable. The whole dataset was divided into training group and testing group at the ratio of 8:2, and predictive performance was compared among six different algorithms. Algorithms with higher model performance (top 3) were selected to establish the ensemble prediction model, and SHAP was employed to interpret of the model. Results: Three algorithms (SVR, GBRT and RF) with high R2 score (0.676, 0.670 and 0.656, respectively) were selected to construct the ensemble model at the ratio of 6:3:1. The model with R2=0.720, MAE=3.628, MSE=22.571, absolute accuracy of 83.93% and relative accuracy of 60.71% was obtained, which performed better in model fitting and had better prediction accuracy than any single algorithm. The feature importance and direction of each variable were visually demonstrated by SHAP values, in which teicoplanin administration and renal function were the most important factors. Conclusions: We firstly adopted machine learning approach to predict the teicoplanin trough concentration, and interpreted the prediction model by SHAP method, which is of great significance and value for clinical medication guidance.